COVID-19 Vaccines’ Protection Over Time and the Need for Booster Doses; a Systematic Review - Dadras, Omid; SeyedAlinaghi, SeyedAhmad; Karimi, Amirali; Shojaei, Alireza; Amiri, Ava; Mahdiabadi, Sara; Fakhfouri, Amirata; Razi, Armin; Mojdeganlou, Hengameh; Mojdeganlou, Paniz; Barzegary, Alireza; Pashaei, Zahra; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: Controversies existed regarding the duration of COVID-19 vaccines’ protection and whether receiving the usual vaccine doses would be sufficient for long-term immunity. Therefore, we aimed to systematically review the studies regarding the COVID-19 vaccines’ protection three months after getting fully vaccinated and assess the need for vaccine booster doses. Methods: The relevant literature was searched using a combination of keywords on the online databases of PubMed, Scopus, Web of Science, and Cochrane on September 17th, 2021. The records were downloaded and the duplicates were removed. Then, the records were evaluated in a two-step process, consisting of title/abstract and full-text screening processes, and the eligible records were selected for the qualitative synthesis. We only included original studies that evaluated the efficacy and immunity of COVID-19 vaccines three months after full vaccination. This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement to ensure the reliability of results. Results: Out of the 797 retrieved records, 12 studies were included, 10 on mRNA-based vaccines and two on inactivated vaccines. The majority of included studies observed acceptable antibody titers in most of the participants even after 6 months; however,it appeared that the titers could also decrease in a considerable portion of people. Due to the reduction in antibody titers and vaccine protection, several studies suggested administering the booster dose, especially for older patients and those with underlying conditions, such as patients with immunodeficiencies. Conclusion: Studies indicated that vaccine immunity decreases over time, making people more susceptible to contracting the disease. Besides, new variants are emerging, and the omicron variant is continuing to spread and escape from the immune system, indicating the importance of a booster dose.